Rest for the wicked - Hart, Ellen (Hart, Ellen. Jane Lawless mystery., 2012)
Receiving an urgent message from hospitalized partner Andy Nolan's nephew, who is killed minutes later, restaurateur and private investigator Jane Lawless embarks on a solo quest to identify the culprit and the victim's link to other killings.